Clinical characteristics and management of functional neurological disorders (FND) mimicking stroke in emergency settings: a functional stroke mimic cases - Caruso, Paola; Radin, Yvonne; Mancinelli, Laura; Quagliotto, Magda; Lombardo, Tiziana; Pavan, Stefania; Catalan, Mauro; Clarici, Andrea; Bulfon, Matteo; Benussi, Alberto; Manganotti, Paolo (Frontiers in Neurology, 2024)
FNDs mimicking a stroke represent a growing challenge in the emergency department (ED).A comprehensive diagnostic approach involving clinical evaluation and neuroimaging is essential to differentiate stroke from mimics. The safety profile of thrombolysis justifies its use where FNDs cannot be ruled out. This approach highlights the need for more precise diagnostic tools and protocols to improve patient care and reduce unnecessary treatments.Distinguishing FNDs from actual cerebrovascular events is critical yet difficult, particularly under time constraints. Given the urgency and potential severity of strokes, intravenous thrombolysis is frequently administered even when FNDs cannot be definitively excluded. This retrospective study analyzed data of participants admitted to the Trieste University Hospital Stroke Unit between January 2018 and December 2022, focusing on those presenting with sudden-onset focal neurological deficits mimicking a stroke, with some presenting within the reperfusion treatment window (<4.5 hours from symptoms onset). We obtained detailed clinical evaluations and neuroimaging, and administered thrombolytic therapy in selected cases.We included 84 participants presenting with stroke mimics (average age of 45 yo) predominantly female (65.5%). Most common presentations: hemiparesis or hemisensory loss (75%), speech disorder (10.7%), vertigo/gait disorders (4.8%). History of psychiatric disorders was found in 32,1% of cases, and 48.8% had prior neurological disease or stroke risk factors. Advanced neuroimaging was performed in 43 cases yielding normal or nonspecific results. Thrombolysis was safely administered in 31%. Patients mostly recovered within the first 24 hours from admission (44.7%). We compared this FND's sample with 291 patients with mild ischemic stroke (NIHSS ≤7).